Onychophagia: A nail-biting conundrum for physicians. (17th February 2017) - Halteh, Pierre; Scher, Richard K.; Lipner, Shari R.
Abstract: Onychophagia, defined as habitual nail biting, is a common disorder affecting 20–30% of the population and all age groups. It may lead to significant psychosocial problems, have a negative impact on quality of life, and cause complications involving both the nail unit and the oral cavity. The objective of this paper is to review the prevalence, etiology, history, physical examination, complications and management of nail biting. Since onychophagia is a challenging disorder to treat, a multi-disciplinary approach should be taken involving dermatologists, internists, pediatricians, psychiatrists and dentists.